Utilisation of Library and Information Services in the Judiciary of Uganda - Bukirwa, Joyce; Nanfuka, Reges (Regional Institute of Information and Knowledge Management, 2020)
Rationale of Study – The purpose of this study was to examine the utilisation of library and information services in the Judiciary of Uganda. It was based on the premise that if library and information services in the Judiciary of Uganda are well utilised, effective administration of justice in Uganda would be achieved.Methodology – The study was guided by Saracevic-Kantor theory of use-oriented value of library and information services. Participants were drawn from two (2) selected libraries namely, the High Court (criminal division) and the Supreme Court libraries. These are the oldest and have the biggest collection compared to the rest of the judiciary libraries. Given a population of five (5) librarians (2 from Supreme court library and 3 from the High Court library), interviews were held with four (4) librarians, two from each of the libraries.Findings – The study established that both the High Court and Supreme Court libraries provide a wide range of services including current awareness, referral, research, selective dissemination of information, Internet, photocopying and newspaper clipping services. The services were regularly utilised across the libraries. However, only 47% of the users were very satisfied with the services, followed by 31% that were satisfied. Some of the challenges affecting the utilisation of library and information services in the Judiciary of Uganda include poor Internet connectivity, inadequate current information, insufficient funding, and limited library facilities.Implications – This study recommends strengthening of library and information services across the Judiciary by digitising the information resources, system-wide automation, training of library users, improving Internet connectivity, increasing funding for library services, and formulation and implementation of a Judiciary of Uganda library policy.Originality – This study is an addition to the scanty literature about judiciary library services, most especially in sub-Saharan Africa. The study ascertains the need for strengthening library and information services in judiciaries.